(untitled) (Research, Society and Development, 2024)
This study’s research object is the photosonic resource called Recupero®, intended for the treatment of people affected by fibromyalgia. Fibromyalgia is a disease that has a major negative impact on patients’ quality of life, as existing treatments appear to be palliative given the level of pain complaints presented by treated patients. The objective of the research is to present Recupero® as an innovative and effective device in the treatment of fibromyalgia, whose function is to emit laser and ultrasound simultaneously on the palms of patients’ hands. This is a case study, supported by a bibliographical review, whose sources, which are still scarce, originate from publications by the Optical Institute of USP – São Carlos, the body responsible for the patent of the device and the research carried out. All the data evaluated leads us to believe that the improvement varies from 50/60 to 90% in just 10 sessions. In this sense, it can be concluded that the device is efficient in terms of what it proposes, presenting results such as a general reduction in pain, improvement in mood, anxiety, intracranial pressure, physical capacity and sleep, which has a decisive impact on the quality of subjects’ lives.